Gastric cancer risk in the elderly is associated with omeprazole use and inversely associated with aspirin use - Gingold-Belfer, Rachel; Issa, Nidal; Boltin, Doron; Beloosesky, Yichayaou; Koren-Morag, Nira; Meyerovitch, Joseph; Sharon, Eran; Peleg, Noam; Schmilovitz-Weiss, Hemda (European journal of gastroenterology & hepatology, 2023)
The association between long-term omeprazole use and gastric cancer (GC) risk is controversial. The aim of this study was to investigate the incidence of GC in elderly community-dwelling omeprazole chronic users with/without aspirin compared to non-users. The registry of a large health management organization was searched for all community-dwelling members aged ≥65 years from January 2002 to December 2016. Data on demographics, background parameters, and chronic omeprazole and aspirin use (>11 prescriptions/year) were retrieved. Those diagnosed with new-onset GC during the study period (from January 2003) were identified. Of 51 405 subjects who met the inclusion criteria, 197 were diagnosed with GC during a mean follow-up period of 8.74 ± 4.16 years. This group accounted for 0.7% of PPI chronic users (72/11 008) and 0.3% (125/40 397) of nonusers (P < 0.001). GC risk was directly associated with omeprazole chronic use [hazard ratio (HR) 2.03, 95% confidence interval (CI): 1.51-2.73, P < 0.001] and inversely associated with aspirin chronic use (HR 0.55, 95% CI: 0.40-0.75, P < 0.001). Each year of omeprazole use increased GC risk by 9%, and each year of aspirin use decreased GC risk by 10% among omeprazole chronic users. The lowest rate of GC was found in omeprazole nonusers/ aspirin chronic users, and the highest, in omeprazole chronic users/aspirin nonusers. Higher GC rate was associated with omeprazole chronic use and inversely associated with aspirin chronic use relative to omeprazole nonuse in community-dwelling elderly.